Does hosting a sport event promotes the city among athletes as a tourist destination? - M. Alguacil; C. Pérez-Campos; S. Aguado Berenguer; J. Boquera (Universidad de Murcia, 2016)
The organization of events by the cities have different implications, including that athletes who participate in it can know the city and may have intentions of returning to it as tourists or recommend it. This work aims to analyze the predictors of the future intentions of athletes regarding the host city of the event. A questionnaire was administered to 99 athletes in the 12ª World Championship indoor athletics, held in the city of Valencia. The average age is 25.36 years with 59.6% women. The proposed model was significant. The quality dimensions of tangibles and security, and the overall satisfaction and perceived value were significant, therefore, event managers and those responsible for the area of tourism, should get the quality in these areas to increase the future intentions of the athletes regarding the city.